Food waste measurement as a tool for prevention and reduction: A case study from a hotel in Colombo, Sri Lanka - CGIAR Research Program on Water, Land and Ecosystems; International Water Management Institute (CGIAR Research Program on Water, Land and Ecosystems, 2021)
The amount of food waste generated in Local Authority areas of Sri Lanka ranges between 50% and 76% of the total municipal solid waste, with an average of 56% (FAO and IWMI 2021a). The total food waste generated is estimated to be nearly 4,000 tons/day (Arachchige et al. 2019; FAO and IWMI 2021b). In 2020, a study conducted by the Food and Agriculture Organization of the United Nations (FAO) and the International Water Management Institute (IWMI) focusing on three major waste disposal centers in the Western Province of Sri Lanka – Karadiyana, Kerawalapitiya and Kaduwela – revealed that about 724 tons of the total waste generated in a day is food waste (i.e., 55% of total waste).